Green Synthesis of Nanoparticles from Flower Extracts: Innovative Applications in Floriculture - , Shrejal Tiwari, Pooja A, Gaurav Sharma, Priyanka Sharma (Archives of Current Research International, 2025)
This review explores about green synthesis of nanoparticles from flower extracts. Green synthesis has gathered significant attention as an environmentally friendly and sustainable approach for the synthesis of a variety of nanomaterials including, metal/metal oxide nanoparticles and bioinspired materials. Flowers are rich in secondary compounds like pigments, volatile molecules which add to fragrance and hold substantial importance predominantly in the context of disease treatment through 'Pushpa Ayurveda' or floral therapy. These phytochemicals from flowers act as efficient reducing and stabilizing agents and offer a unique medium for synthesizing a variety of metal and metal oxide nanoparticles, including gold, silver, copper, zinc, iron, and cadmium. This synthesis process typically occurs at ambient temperatures, making it environmentally friendly and free from the production of toxic by-products. Nanoparticles thus formed can be used to carry ethylene action inhibitors, control the growth and development of microorganisms and to introduce a new generation of packaging material that controls gases and harmful UV rays, while increasing strength, quality and packaging appearance. Furthermore, there are several examples of nanoparticles extracted from bougainvillea that are used in cosmetic industries, in the field of biomedical science, silver NP synthesized from Hymenocallis littoralis exhibits strong antimicrobial properties, making them useful in treating infections and enhancing the effectiveness of antibiotics. Gold nanoparticles derived from Hibiscus rosa-sinensis are utilized in targeted drug delivery and photothermal therapy for cancer treatment. Thus, Flower-derived nanoparticles find applications in biomedical science, offering health benefits, nanoencapsulation, prolonged vase life for cut flowers, packaging, and diverse uses in various fields.